Tuning of the Mg Alloy AZ31 Anodizing Process for Biodegradable Implants - Zaffora, Andrea; Di Franco, Francesco; Virtù, Danilo; Carfì Pavia, Francesco; Ghersi, Giulio; Virtanen, Sannakaisa; Santamaria, Monica (ACS Applied Materials and Interfaces, 2021)
Coatings were grown on the AZ31 Mg alloy by a hard anodizing process in the hot glycerol phosphate-containing electrolyte. Anodizing conditions were optimized, maximizing corrosion resistance estimated by impedance measurements carried out in Hank's solution at 37 °C. A post anodizing annealing treatment (350 °C for 24 h) allowed us to further enhance the corrosion resistance of the coatings mainly containing magnesium phosphate according to energy-dispersive X-ray spectroscopy and Raman analyses. Gravimetric measurements revealed a hydrogen evolution rate within the limits acceptable for application of AZ31 in biomedical devices. In vitro tests demonstrated that the coatings are biocompatible with a preosteoblast cell line.
CRIS-Team Scopus Importer:2021-04-19
Keywords: biomedical; corrosion resistance; electrochemical impedance spectroscopy; hard anodizing; Mg alloy